2010
DOI: 10.1016/j.jbiomech.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Variation of hamstrings lengths and velocities with walking speed

Abstract: Crouch gait, one of the most prevalent movement abnormalities among children with cerebral palsy, is frequently treated with surgical lengthening of the hamstrings. To assist in surgical planning many clinical centers use musculoskeletal modeling to help determine if a patient's hamstrings are shorter or lengthen more slowly than during unimpaired gait. However, some subjects with crouch gait walk slowly, and gait speed may affect peak hamstring lengths and lengthening velocities. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…Previous studies showed increases in peak hamstring length with increasing walking speed [25,26]. In this study, walking speed in mimicked crouch gait was significantly faster than that in patients with crouch gait (p<0.001).…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies showed increases in peak hamstring length with increasing walking speed [25,26]. In this study, walking speed in mimicked crouch gait was significantly faster than that in patients with crouch gait (p<0.001).…”
Section: Discussionsupporting
confidence: 48%
“…4,5 Satisfying short-term results were complemented with reports of increased pelvic tilt and genu recurvatum as signs of overcorrection. 8,9 Furthermore, recurrent hamstring tightness during growth is one reason considered for the recurrence of flexed knee gait. 1 Musculoskeletal analysis revealed that only one-third of the hamstrings in children with flexed knee gait are short and slow.…”
mentioning
confidence: 99%
“…Therefore, they have greater efficiency and are used for activities that need strength [2,33]. A review of the literature has shown that few studies [1,8,17,20,29] go beyond a description of muscle length changing during a crouching gait, and no references were found in sport application and above all in knee up move analysis.…”
Section: Discussionmentioning
confidence: 99%